Bowls and Burials – an Update from Grand Bay, Carriacou, West Indies: May–June 2011 - Kaye Quetta; Scott Fitzpatrick; Mary Harris; Michiel Kappers (Papers from the Institute of Archaeology, 2012)
From May 23 to June 23 2011 Kaye, Fitzpatrick and Kappers directed a team comprising four staff members from England, The Netherlands and the U.S., together with 27 students from various American universities and UCL's Institute of Archaeology, to conduct the sixth season of archaeological investigation at the coastal site of Grand Bay, Carriacou (fig. 1). Our major goal this year was to finalise the excavation of three previously opened 5×5 metre trenches (nos 592, 415 and 446) (fig. 2) (see summaries in Fitzpatrick et al. 2009a, 2009b; Kaye et al. 2009), while training students in fieldwork techniques and continuing our community outreach work by encouraging site visits, giving talks to schools, organising an exhibition of small finds for a public open day and conducting a series of television, radio, and newspaper interviews in order to raise public awareness and encourage interest in the archaeological heritage of the island. The Carriacou Historical Society (CHS) also requested us to prepare a report on the possible impact of a proposed "Free Port" coastal development on archaeological sites along the southeastern part of the island. The brief results of the 2011 project are presented in the following.
Keywords: human remains; burial; excavation report